Practical Islamic input in Orthopaedics Undergraduate Medical Curricula - Zulkifly, Ahmad Hafiz; Mohd Yusof, Nazri; Khalid, Kamarul Ariffin; Che Ahmad, Aminudin; Zakaria@Mohamad, Zamzuri; Aziz, Mohd Yusof; Mohamed Amin, Mohamed Azril; Awang, Mohd Shukrimi; Kasule, Omar Hassan (Faculty of Medicine, International Islamic University Malaysia, 2004)
The International Islamic University of Malaysia (IIUM) was founded in 1983 upon a renewed awareness of the perennial values of the teachings in the Al-Quran and Sunnah and is dedicated to the reorientation of the ummah and mankind towards this end. The first Mission Statement of IIUM stated that it would ‘…undertake the special and greatly needed task of reforming the contemporary Muslim mentality and integrating Islamic Revealed Knowledge and the Human Sciences in a positive manner’. When it was first founded, IIUM had faculties only in the Human and Social Sciences. In 1995, the Kulliyyah of Medicine (Kulliyyah al-Tabb) was established and the fist batch of 69 medical undergraduates started their medical education in 1997.